Resolving Salmonella infection reveals dynamic and persisting changes in murine bone marrow progenitor cell phenotype and function. Issue 8 (11th June 2014) - Ross, Ewan A.; Flores‐Langarica, Adriana; Bobat, Saeeda; Coughlan, Ruth E.; Marshall, Jennifer L.; Hitchcock, Jessica R.; Cook, Charlotte N.; Carvalho‐Gaspar, Manuela M.; Mitchell, Andrea M.; Clarke, Mary; Garcia, Paloma; Cobbold, Mark; et al.
<x xml:space="preserve">Abstract</x> The generation of immune cells from BM precursors is a carefully regulated process. This is essential to limit the potential for oncogenesis and autoimmunity yet protect against infection. How infection modulates this is unclear. Salmonella can colonize systemic sites including the BM and spleen. This resolving infection has multiple IFN‐γ‐mediated acute and chronic effects on BM progenitors, and during the first week of infection IFN‐γ is produced by myeloid, NK, NKT, CD4+ T cells, and some lineage‐negative cells. After infection, the phenotype of BM progenitors rapidly but reversibly alters, with a peak ∼30‐fold increase in Sca‐1hi progenitors and a corresponding loss of Sca‐1lo/int subsets. Most strikingly, the capacity of donor Sca‐1hi cells to reconstitute an irradiated host is reduced; the longer donor mice are exposed to infection, and Sca‐1hic‐kitint cells have an increased potential to generate B1a‐like cells. Thus, Salmonella can have a prolonged influence on BM progenitor functionality not directly related to bacterial persistence. These results reflect changes observed in leucopoiesis during aging and suggest that BM functionality can be modulated by life‐long, periodic exposure to infection. Better understanding of this process could offer novel therapeutic opportunities to modulate BM functionality and promote healthy aging.